2018
DOI: 10.1093/hmg/ddy215
|View full text |Cite
|
Sign up to set email alerts
|

Cofilin-1 phosphorylation catalyzed by ERK1/2 alters cardiac actin dynamics in dilated cardiomyopathy caused by lamin A/C gene mutation

Abstract: Hyper-activation of extracellular signal-regulated kinase (ERK) 1/2 contributes to heart dysfunction in cardiomyopathy caused by mutations in the lamin A/C gene (LMNA cardiomyopathy). The mechanism of how this affects cardiac function is unknown. We show that active phosphorylated ERK1/2 directly binds to and catalyzes the phosphorylation of the actin depolymerizing factor cofilin-1 on Thr25. Cofilin-1 becomes active and disassembles actin filaments in a large array of cellular and animal models of LMNA cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 101 publications
(107 reference statements)
4
67
0
2
Order By: Relevance
“…These aggregates compromise proper targeting of desmoplakin (in blue) to the desmosomes and consequently their stabilization, thus also affecting indirectly the stability of fascia adherens and gap junctions and their components. In addition, or alternatively, desmin network destabilization could influence, through the linker plectin, the other two cytoskeletal networks, actin microfilaments and microtubules, thus contributing to the observed mislocalization of plakoglobin (in green) or connexin-43 (in yellow), consistent with the previously reported effects in actin [46] and microtubule [47,48] cytoskeleton in the Lmna H222P/H222P mouse cardiomyocytes. Similarly, desmin network destabilization and aggregation leads to the expected mitochondrial defects due to loss of proper desmin function [26] (B).…”
Section: Accepted Manuscriptsupporting
confidence: 89%
See 1 more Smart Citation
“…These aggregates compromise proper targeting of desmoplakin (in blue) to the desmosomes and consequently their stabilization, thus also affecting indirectly the stability of fascia adherens and gap junctions and their components. In addition, or alternatively, desmin network destabilization could influence, through the linker plectin, the other two cytoskeletal networks, actin microfilaments and microtubules, thus contributing to the observed mislocalization of plakoglobin (in green) or connexin-43 (in yellow), consistent with the previously reported effects in actin [46] and microtubule [47,48] cytoskeleton in the Lmna H222P/H222P mouse cardiomyocytes. Similarly, desmin network destabilization and aggregation leads to the expected mitochondrial defects due to loss of proper desmin function [26] (B).…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…cytoskeleton to actin microfilaments and microtubules though plectin at least, it is not surprising to link their defects to the pathology of the Lmna H222P/H222P [46][47][48] or TAC [61] mouse models of cardiomyopathy. We also revealed that in Lmna H222P/H222P hearts desmin exhibits a different PTM status, as indicated by the presence of more acidic desmin isoforms in 2-D Western blot, compatible with increased phosphorylation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Thus, mutations in genes encoding LINC complex proteins could alter in a tissue-specific manner transcription factors expression and/or alter expression pattern of tissue-specific genes ( Dialynas et al, 2010 ). For example, such alterations are more and more described for laminopathies with the hyperactivation of the ERK (extracellular signal-regulated kinase) pathway in cardiomyopathy caused by LMNA mutations ( Chatzifrangkeskou et al, 2018 ) or the overexpression of SMAD6, an inhibitor of the BMP signaling pathways, as a cause of accelerated myogenic differentiation of LMNA mutated cells ( Janin et al, 2018 ).…”
Section: Mutations Pathogenesis Hypothesismentioning
confidence: 99%
“…We used transthoracic echocardiography to determine the cardiac function of Lmna H222P/H222P male mice. While the cardiac structure and function were not statistically different at 3 months of age, at 6 months of age, Lmna H222P/H222P male mice have increased left ventricular diameters, and decreased fractional shortening (FS) compared with wild type animals ( Figure 1A) (8,9,16). Left ventricular dilatation in Lmna H222P/H222P male mice at 6 months of age was demonstrated by histopathological analysis ( Figure 1B).…”
Section: Depressed Left Ventricular Function In Lmna H222p/h222p Mousmentioning
confidence: 96%
“…We largely contributed in understanding the metabolic and physiological mechanisms regulating cardiac function and energy balance in EDMD, both in animal models and in patient's tissues. These include abnormal regulation of the mitogenactivated protein kinase (MAPK) signaling cascade (6,7), altered actin dynamics (8), altered Wnt/βcatenin signaling (9), fibrosis (10), NAD signaling (11) and AKT/mTOR signaling (12). Despite the growing understanding of the pathogenesis of EDMD as well as the discovery of novel therapeutic for the disease (7,(9)(10)(11)(12)(13), little is known on the overall benefit of these treatments on the performance of the animals.…”
Section: Introductionmentioning
confidence: 99%